The first report of composition and occurrence of myxomycete assemblages in protected and unprotected plantation forests: a comparative study in Thai Nguyen City, Northern Vietnam - John Redeña-Santos; Duong Van Thao; Martin Schnittler; Nikki Heherson Dagamac (Plant Ecology and Evolution, 2018)
Background and aims – In spite of the cosmopolitan distributions of myxomycetes, relatively few studies have been conducted in subtropical forests of Southeast Asia, particularly in Northern Vietnam, where comprehensive reports of myxomycetes are lacking up to this date. Hence, a rapid biodiversity assessment was conducted in protected and unprotected plantation forests of Thai Nguyen City to compare the species composition of myxomycete communities between the two different forest management types.Methods – A total of 360 substrate samples were haphazardly collected within 5 m × 5 m plots established within three protected and three unprotected forests. The moist chamber cultures prepared from these samples were regularly checked for myxomycete fructifications over a period of 12 weeks. Analyses of diversity (species richness) and community composition were performed using the software EstimateS and the vegan package in R.Key results – The study yielded a total of 505 records representing 54 species belonging to 17 genera. All species recorded herein were new records for Northern Vietnam; among them five were new for the entire country. The rarefaction curves showed higher numbers of myxomycete species to be expected for protected forest (43.0) in comparison to unprotected forests (39.4). However, calculations of species diversity indices showed higher values in unprotected forest than in protected forest. The species composition between the two forest types showed clear overlaps with many shared (56%) species. Conclusions – Forest conservation strategies do not affect freely dispersing myxomycetes implicating that spore dispersal of myxomycetes is caused not only by natural factors but also by anthropogenic activities. The production of high number of myxomycete species for this study seems to point out that the subtropical forests of Vietnam harbours many undiscovered myxomycete species for Southeast Asia.